When ambush marketing is beneficial to sponsorship awareness: creating sponsor distinctiveness using exclusivity and brand juxtaposition. Issue 15 (13th October 2017) - Weeks, Clinton S.; O'Connor, Peter J.; Martin, Brett A. S.
ABSTRACT: Ambush marketing is a contentious practice whereby brands communicate an association with an event without being an official sponsor. Those involved in sponsorship commonly try to limit it by restricting ambusher activity in event contexts. We introduce theoretical ideas around distinctiveness to explain that sponsors may actually fare better in terms of awareness outcomes when ambushers are present in the event context, if they strategically use ambusher presence to highlight their own distinctive sponsor status. Across two experiments we show that sponsor distinctiveness can be achieved by communicating sponsorship exclusivity in ambusher presence, and by facilitating juxtaposition of sponsor and ambusher messages. Results include increased recall to sponsor cues, and reduced recall to ambusher cues. The findings suggest ambusher restrictions may sometimes be counter-productive.